2021
DOI: 10.1002/dvdy.425
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of inwardly rectifying potassium channels and their gene expression in zebrafish embryos

Abstract: Background Inwardly rectifying potassium channels are essential for normal potassium homeostasis, maintaining the cellular resting membrane potential, and regulating electrolyte transportation. Mutations in Kir channels have been known to cause debilitating diseases ranging from neurological abnormalities to renal and cardiac failures. Many efforts have been made to understand their protein structures, physiological functions, and pharmacological modifiers. However, their expression and functions during embryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…However, many of the zebrafish k2p genes were temporally expressed at specific anatomic structures such as notochord ( kcnk6 ), somites ( kcnk4a ), pectoral fin ( kcnk4b , kcnk5b ), caudal fin fold ( kcnk4b ), and pancreas ( kcnk3b , kcnk9 ). This phenomenon is similar to zebrafish KCa and Kir channel genes, 48,55 suggesting that k2p genes are required not only for a specific physiological need but also for instructional signaling during developmental processes.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…However, many of the zebrafish k2p genes were temporally expressed at specific anatomic structures such as notochord ( kcnk6 ), somites ( kcnk4a ), pectoral fin ( kcnk4b , kcnk5b ), caudal fin fold ( kcnk4b ), and pancreas ( kcnk3b , kcnk9 ). This phenomenon is similar to zebrafish KCa and Kir channel genes, 48,55 suggesting that k2p genes are required not only for a specific physiological need but also for instructional signaling during developmental processes.…”
Section: Discussionsupporting
confidence: 57%
“…The six subtypes of K2P genes already existed in the invertebrates before the dawn of vertebrates (Figure 17A), similar to Kir channel genes. 48 After two rounds of WGDs (2Rs), all genes were doubled twice, which led to four copies of each gene. However, some of the ohnologs were lost immediately.…”
Section: Evolutionary History Of Vertebrate K2p Channel Genesmentioning
confidence: 99%
“…However, the underlying ion channels and connexins that generate these signals are unknown. Our recent gene expression analysis of calcium-gated potassium channels (KCa) and inwardly rectifying potassium channels (Kir) revealed that many ( kcnn1b , kcnn3 , kcnma1a , kcnma1b , kcnmb2b , kcnmb3 , kcnj4 , kcnj2a , kcnj2b , kcnj11 , kcnj5 , kcnj21 ) have a somite-specific expression at similar developmental stages [ 37 , 38 ]. Their presence in the developing somites may indicate that these channel activities underlie the tissue-level bioelectricity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, abundant ion regulators in different cell types within zebrafish somites and fins can be identified using this technique. Alternatively, whole mount in situ hybridization can be performed systematically, to examine their expression during zebrafish embryogenesis, as was performed in the case of the potassium channel gene subfamilies [ 281 , 282 ]. Once their gene expression is known, cell- and/or tissue-specific multiplexing gene knockout or knockdown by CRISPR can be used to examine certain ion regulators’ function in developmental patterning [ 283 , 284 , 285 , 286 , 287 ].…”
Section: Prospects and Opportunities: Future Directions For Developme...mentioning
confidence: 99%